Cabbage Palm Caterpillar, Litoprosopus futilis (G. & R.) (Insecta: Lepidoptera: Noctuidae: Ophiderinae): EENY095/IN252, 7/1999 - Dekle, Geo Wallace (EDIS, 2002)
This document is EENY-095 (originally published as DPI Entomology Circular No. 75), one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: July 1999. EENY095/IN252: Cabbage Palm Caterpillar Litoprosopus futilis (Grote & Robinson) (Insecta: Lepidoptera: Erebidae: Eulepidotinae) (ufl.edu)